Chromium-molybdenum-vanadium-titanium microalloyed wear-resistant steel and production method thereof

Through the Cr-Mo-V-Ti component system and finely controlled production process, micron-scale Ti (CN) and nano-scale Mo-Ti-V carbonitride precipitation phases are formed, which solves the problem of insufficient strength and wear resistance of wear-resistant steel in the existing technology and realizes high-strength and high-wear-resistant martensitic wear-resistant steel.

CN120776204APending Publication Date: 2025-10-14PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511002576.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, there are few methods for enhancing the wear resistance of martensitic wear-resistant steel by using micron-scale TiC and at the same time using nano-scale carbide precipitation phases of V, Ti, and Mo to improve the strength and wear resistance of martensitic wear-resistant steel.

Method used

By adopting the Cr-Mo-V-Ti composition system and developing TiC particle-reinforced martensitic wear-resistant steel on the hot rolling production line, the chemical composition and production process of the steel are controlled, including converter smelting, LF refining, RH refining, continuous casting, slab heating, rolling, laminar cooling and tempering, to form micron-sized Ti (CN) hard particles and nano-sized Mo-Ti-V composite carbonitride precipitation phase.

Benefits of technology

The yield strength, tensile strength and hardness of martensitic wear-resistant steel are significantly improved, the wear resistance of the material is enhanced, and good tempering stability is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of high-strength hot continuous rolling steel, and particularly relates to chromium-molybdenum-vanadium-titanium microalloyed wear-resistant steel and a production method thereof. In order to further improve the strength, hardness and wear resistance of the martensitic wear-resistant steel, the invention provides the martensitic wear-resistant steel which comprises the following chemical components in percentage by mass: 0.3 to 0.4 percent of C, 0.1 to 0.3 percent of Si, 1.5 to 2.0 percent of Mn, less than or equal to 0.015 percent of P, less than or equal to 0.005 percent of S, 0.01 to 0.05 percent of Als, 0.3 to 0.4 percent of Cr, 0.15 to 0.30 percent of Mo, 0.05 to 0.10 percent of V, 0.4 to 0.8 percent of Ti, 0.01 to 0.012 percent of N and the balance of Fe and inevitable impurities. According to the steel disclosed by the invention, micron-sized Ti (CN) particles and a nano-sized Mo-Ti-V carbonitride precipitated phase are introduced, so that the matrix strength is improved, and the wear resistance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-strength hot-rolled steel, and particularly relates to a chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel and a production method thereof. Background Art

[0002] Wear-resistant steel is widely used in the engineering machinery industry, particularly martensitic wear-resistant steel, which, due to its high strength and hardness, accounts for a large proportion of wear-resistant steel products. Recent research has found that the introduction of micron-sized hard Ti(CN) particles into wear-resistant steel can further enhance the material's wear resistance, particularly in applications subject to abrasive wear, such as coal conveyors, mine car bodies, and conveying pipelines. This is primarily due to the hardness of Ti(CN) particles exceeding HV3000, far exceeding that of the steel matrix, which helps suppress wear marks and furrows.

[0003] At present, patent CN118854171A discloses a martensitic wear-resistant steel and its preparation method. The composition of the steel is: C: 0.38% to 0.42%, Ti: 0.75% to 0.8%, Mo: 0.2% to 0.28%, V: 0.38% to 0.4%, Mn: 1.58% to 2%, Si: 0.084% to 0.1%, P < 0.015%, S < 0.002%, and the balance is Fe and inevitable impurities. The martensitic wear-resistant steel provided by this invention has C, Mn and Si as the main elements, and further controls the addition amount of Ti, Mo and V elements, thereby achieving composite strengthening between the elements, suppressing the growth of austenite crystals, refining martensite crystals and improving the tempering stability of the martensitic wear-resistant steel, thereby improving the strength and toughness of the martensitic wear-resistant steel.

[0004] For example, patent CN109706399A discloses a high-titanium wear-resistant steel and its preparation method. The steel's composition is as follows: C: 0.15-0.28%, Si: 0.18-0.22%, Mn: 0.9-1.5%, S≤0.015%, P≤0.020%, Mo: 0.15-0.32%, Ti: 0.30-0.6%, Als: 0.02-0.06%, and the remainder is Fe and unavoidable impurities. The wear-resistant steel with this invention's composition ratio can significantly improve the wear resistance of the steel plate while maintaining hardness.

[0005] In addition, patent CN115449702A also discloses a method for preparing high-titanium wear-resistant steel, the chemical composition of which is: C: 0.69-0.77%, Si: 1.68-1.85%, Mn: 2.22-2.48%, Cr: 0.65-0.79%, S<0.035%, P<0.040%, Al: 0.03-0.06%, Ti: 0.8-1.0%, and the balance is Fe and inevitable impurities. The molten steel is treated outside the furnace and then poured into castings. After heat treatment, the obtained high-titanium wear-resistant steel has high hardness, good toughness and excellent wear resistance.

[0006] Although there are many existing technologies for studying martensitic wear-resistant steel, there are few reports on using micron-scale TiC to enhance wear resistance and nano-scale V, Ti, and Mo carbide precipitation phases to improve strength to obtain Cr-Mo-V-Ti wear-resistant steel. Summary of the Invention

[0007] In order to further improve the strength, hardness and wear resistance of martensitic wear-resistant steel, the present invention designs a Cr-Mo-V-Ti composition system and realizes the development of TiC particle-reinforced martensitic wear-resistant steel on a conventional hot rolling production line.

[0008] To achieve the above application objectives, the technical solutions adopted in this application are as follows: In a first aspect, the present invention provides a chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel, the chemical composition of which includes, by mass percentage, C: 0.3-0.4%, Si: 0.1-0.3%, Mn: 1.5-2.0%, P≤0.015%, S≤0.005%, Als: 0.01-0.05%, Cr: 0.3-0.4%, Mo: 0.15-0.30%, V: 0.05-0.10%, Ti: 0.4-0.8%, N: 0.01-0.012%, and the balance is Fe and unavoidable impurities.

[0009] Furthermore, the microstructure of the chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel includes more than 90% martensite by volume, and the rest is ferrite; it contains micron-sized Ti (CN) hard particles larger than 1 μm and nano-sized Mo-Ti-V composite carbonitride precipitation phases smaller than 30 nm.

[0010] Furthermore, the chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel has a yield strength of ≥1000 MPa, a tensile strength of ≥1100 MPa, an elongation of ≥8%, and a hardness of HBW400-500.

[0011] In a second aspect, the present invention provides a method for producing the above-mentioned chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel, comprising the following steps: According to the set chemical composition of the steel, converter smelting, LF refining, RH refining, continuous casting, slab heating, rolling, laminar cooling, coiling and tempering can be carried out in sequence.

[0012] Furthermore, the thickness of the steel ingot after smelting and continuous casting is 200-250 mm.

[0013] Furthermore, the steel slab after continuous casting is heated by hot delivery and hot charging.

[0014] Furthermore, the temperature of the heated steel slab out of the furnace is 1200-1230° C., and the time in the furnace is 180-300 min.

[0015] Furthermore, the heated steel ingot is rolled in two stages, wherein the final rolling temperature of the first stage is ≥1000°C, and the thickness of the intermediate ingot after rolling is 45-55 mm.

[0016] Furthermore, the finishing temperature of the intermediate billet in the second stage rolling is 850-890° C., and the thickness of the steel plate after rolling is 4-16 mm.

[0017] Furthermore, the steel plate is subjected to laminar cooling after rolling. When the thickness of the steel plate is 4 to 10 mm, the steel plate is directly cooled to 150 to 250° C. at a cooling rate of ≥30° C. / s.

[0018] Furthermore, when the thickness of the steel plate is 10.1-16 mm, two-stage cooling is adopted. The steel plate is first cooled to 680-720°C at a cooling rate of ≥10°C / s, air-cooled for 2-4s, and then continued to cool to 150-250°C at a cooling rate of ≥30°C / s.

[0019] Furthermore, the steel plate is tempered after coiling, with a tempering temperature of 580-620°C and a tempering time of 30-40 min.

[0020] Beneficial effects: (1) The present invention provides a chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel, which is based on the existing martensitic wear-resistant steel, introduces micron-sized Ti (CN) particles to improve the wear resistance of the material, introduces nano-sized Mo-Ti-V carbonitride precipitation phase to improve the matrix strength, and further improves the wear resistance.

[0021] (2) The chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel prepared by the present invention has a yield strength of ≥1000 MPa, a tensile strength of ≥1100 MPa, an elongation of ≥8%, and a hardness HBW of 400-500.

[0022] (2) The steel production process provided by the present invention is simple and the tempering stability of the material is good. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clear, the application is further described in detail below in conjunction with the embodiments. Unless otherwise defined, all scientific and technical terms used herein have the same meanings as understood by ordinary technicians in this field.

[0024] In one embodiment of the present invention, a chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel is provided, the chemical composition of which includes, by mass percentage, C: 0.3-0.4%, Si: 0.1-0.3%, Mn: 1.5-2.0%, P≤0.015%, S≤0.005%, Als: 0.01-0.05%, Cr: 0.3-0.4%, Mo: 0.15-0.30%, V: 0.05-0.10%, Ti: 0.4-0.8%, N: 0.01-0.012%, and the balance is Fe and unavoidable impurities.

[0025] The reasons for limiting the main alloying elements in the steel of the present invention are explained below.

[0026] Carbon is a key component of martensite. Increasing the carbon content shifts the CCT curve to the right, delaying the transformation from pearlite to bainite, thereby increasing the martensite content and the carbon content within it, promoting increases in tensile strength and hardness. Furthermore, increasing the carbon content increases the [Ti][C] concentration product, increasing the amount of micron-sized Ti(CN) precipitated during solidification, increasing the number of hard particles in the steel, and improving the material's wear resistance. Therefore, the present invention limits the carbon content to 0.3-0.4%.

[0027] Mn plays a role in solid solution strengthening and improving toughness in steel. Mn can also improve the stability of supercooled austenite, reduce the critical cooling rate, and promote martensitic transformation. However, when the Mn content is too high, it is easy to cause segregation of the casting and affect the uniformity of the structure. Therefore, the Mn content is controlled at 1.5-2.0%.

[0028] Si and Al are important deoxidizing elements. Therefore, some Si and Al are added to the steel to reduce the degree of oxidation in the molten steel, thereby reducing the level of oxide inclusions. Therefore, the present invention requires the addition of 0.1-0.3% Si and 0.01-0.05% AlS (acid-soluble aluminum).

[0029] P and S are inevitable impurity elements in steel. A high P content will segregate at the grain boundaries, increasing the cold brittleness of the steel. A high S content will increase the sulfide inclusion content and reduce the toughness and ductility of the steel. Therefore, the present invention requires that the P and S contents be controlled at ≤0.015% and ≤0.005%, respectively.

[0030] Cr improves the hardenability of steel and promotes martensitic transformation. Therefore, the present invention requires the addition of 0.3-0.4% Cr. Mo improves the hardenability of steel, inhibits pearlite transformation, and promotes martensitic transformation. Mo also refines the carbonitride precipitation phase of the V-Ti composite, increasing the strength of the steel. Therefore, the present invention requires the addition of 0.15-0.30% Mo.

[0031] When the [Ti][C] concentration is high, a eutectic reaction occurs during the solidification phase of the molten steel, forming micron-sized Ti(CN) particles. These particles have a high hardness of up to 3200 HV. When evenly distributed in the matrix, they inhibit the propagation of scratches or furrows caused by abrasive wear on the steel surface, thereby improving the steel's wear resistance. Therefore, the present invention adds a relatively high content of Ti, but limits its content to 0.4-0.8%.

[0032] During hot rolling and tempering, V combines with C and N to form V(CN) nano-precipitates, thereby increasing the strength of the steel. Therefore, the present invention limits the V and N contents to 0.05-0.10% and 0.01-0.012% respectively.

[0033] In addition, elements such as Cr, Mo, V, and Ti can also improve the tempering stability of steel. That is, the above elements can react with carbon and nitrogen during the tempering process to form complex carbonitrides, thereby increasing the strength and hardness of the material and avoiding the reduction in hardness of the steel due to the decomposition of carbon in martensite during the tempering process.

[0034] In another embodiment of the present invention, a production method of the above-mentioned chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel is provided, comprising the following steps: performing converter smelting, LF refining, RH refining, continuous casting, slab heating, rolling, laminar cooling, coiling, and tempering in sequence according to the set steel chemical composition.

[0035] The reasons for the production process limitations are explained below in conjunction with the control requirements for improving the wear resistance of steel described in the present invention.

[0036] First, the present invention requires that the steel billet be delivered to the slab heating furnace using hot delivery and hot charging, with the slab discharge temperature being 1200-1230°C and the furnace time being 180-300 minutes. Because the steel of the present invention contains relatively high levels of hardenability elements such as C, Mn, Cr, Mo, V, and Ti, the steel billet is prone to precipitating coarse martensite during air cooling, increasing its brittleness and the risk of fracture. Therefore, the present invention requires that the steel billet be delivered to the heating furnace using hot delivery and hot charging. Furthermore, during the solidification phase of the molten steel, the steel of the present invention generates a large number of micron-sized Ti(CN) hard particles through a eutectic reaction. To prevent these hard particles from dissolving back in large quantities during the slab heating process, the steel of the present invention should not be heated to excessively high temperatures or furnace times that are too long. It is also not advisable to use excessively low heating temperatures or furnace times that are too short. Otherwise, the microalloying elements such as Cr, Mo, V, and Ti in the steel cannot be fully dissolved, resulting in a reduction in the subsequent precipitation phase content.

[0037] Secondly, the rolling stage adopts a two-stage rolling process, in which the first stage rolling is rolling in the austenite recrystallization zone. This process has requirements for deformation temperature and deformation amount. The rolling temperature is required to be higher than the critical temperature of austenite recrystallization (approximately 950°C). Therefore, the present invention limits the first stage finishing rolling temperature to ≥1000°C. At the same time, the present invention also requires that the thickness of the intermediate billet after the first stage rolling is 45-55 mm, mainly considering that the thickness of the cast billet is 200-250 mm, that is, the cumulative compression ratio is required to be 3.6-5.6. This is to promote austenite recrystallization and achieve austenite structure refinement. The second stage rolling is rolling in the austenite non-recrystallization zone. Increasing the cumulative compression ratio can promote the flattening of the austenite structure, provide sufficient nucleation points for subsequent structure nucleation, and thus promote the refinement of the finished product structure. The finished steel of the present invention has a thickness of 4-16 mm and a cumulative compression ratio of 3.4-11. At the same time, the present invention requires that the final rolling temperature of the second stage rolling be 850-890°C. This is because when the final rolling temperature is too low, the deformation-induced precipitation during the rolling process will be reduced, thereby reducing the strength and hardness of the finished steel. When the final rolling temperature is too high, the structure of the finished steel will coarsen, reducing the strength and plasticity of the steel.

[0038] In addition, phase transformation mainly occurs during laminar cooling. Here, a higher laminar cooling rate (≥30°C / s) and a lower final cooling temperature (150-250°C) are required to promote martensitic transformation. It is worth noting that when the thickness of the finished steel is 10.1-16 mm, the present invention requires that the steel plate be first rapidly cooled to 680-720°C, then air-cooled for 2-4 seconds, and then rapidly cooled to 150-250°C. This is because the steel plate is relatively thick at this time. If it is directly cooled to 150-250°C, the steel plate may return to red, that is, the core of the steel plate is not cooled thoroughly, and the heat in the core of the steel plate diffuses back to the surface, resulting in a high temperature of the steel plate and a coarse structure. The present invention promotes the uniformity of the heat inside the steel plate by adding 2-4 seconds of air cooling, avoiding the problem of the steel plate returning to red.

[0039] Finally, the steel plate is required to be tempered after coiling, with a tempering temperature of 580-620°C and a tempering time of 30 min. The main purpose of tempering is to reduce the residual stress of the steel plate and improve the plasticity of the material by restoring some dislocations in the martensite. In general, during the tempering process, the supersaturated carbon in the martensite will dissolve back to form partial cementite, resulting in a decrease in the strength and hardness of the steel. In order to improve the tempering stability of the material, that is, to avoid a decrease in the strength and hardness of the material, the steel described in the present invention is added with elements such as Cr, Mo, V, and Ti. By forming a carbonitride precipitation phase during the tempering process, the decrease in strength and hardness is avoided, thereby achieving an improvement in tempering stability. The setting of the tempering temperature is mainly based on the consideration that the range of 580-620°C is the suitable precipitation temperature range for the carbonitrides of the above-mentioned microalloying elements.

[0040] Specific examples will be listed below to explain the scheme of the present invention. Those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not specified in the examples, they are carried out according to the techniques or conditions described in the literature in this area or according to the product specifications. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0041] Test Example Preparation of wear-resistant steel Table 1 shows the compositions of the embodiments of the present invention and the comparative examples, Table 2 shows the production process parameters of the embodiments of the present invention and the comparative examples, and Table 3 shows the microstructures and performance indicators of the steels of the embodiments of the present invention and the comparative examples.

[0042] The wear-resistant steels described in Examples 1 to 3 of the present invention undergo conventional converter smelting, LF refining, RH refining, continuous casting, slab heating, rolling, laminar cooling, coiling, and tempering, with strict control of the production process during the hot rolling process. The finished steel plates have a yield strength ≥1000 MPa, a tensile strength ≥1100 MPa, an elongation ≥8%, and a hardness HBW of 400-500. The microstructure is primarily martensite, also containing a small amount of ferrite, and has micron-sized Ti(CN) and nanometer-sized Mo-Ti-V composite carbonitride precipitates.

[0043] The chemical composition of the steel in Comparative Example 1 contained relatively low carbon and titanium contents of 0.16% and 0.38%, respectively, below the required values ​​of 0.3-0.4% and 0.4-0.8%. Consequently, the content of micron-sized Ti(CN) hard particles precipitated in the finished steel was reduced, as was the number of nanoscale Mo-Ti-V composite carbonitride precipitates. This resulted in lower strength, hardness, and wear resistance in the finished steel.

[0044] The chemical composition of the steels in Comparative Examples 2 and 3 met the requirements. However, the laminar cooling rate of the steel in Comparative Example 2 was too low, at 18°C / s, which was ≥30°C / s below the required value. The coiling temperature was too high, at 621°C, which was 150-250°C above the required value. This temperature range falls within the ferrite-pearlite transformation zone. Therefore, the microstructure of the steel in Comparative Example 2 is composed of ferrite and pearlite, and its strength and hardness are far below the requirements for martensitic wear-resistant steel.

[0045] The coiling temperature of the steel in Comparative Example 3 is 403°C, which is 150-250°C higher than the required value. This temperature range is in the bainite transformation range (above the martensite temperature range, bainite first, then pearlite, around 400°C is in the bainite range, and above 550°C is in the pearlite range). Therefore, the microstructure of the steel in Comparative Example 3 is ferrite plus bainite, and its strength and hardness are both lower than the requirements of martensitic wear-resistant steel.

[0046] No microalloying elements such as Cr, Mo, and V are added to the steel of Comparative Example 4. Therefore, the tempering stability of the steel of Comparative Example 4 during tempering is relatively low. The carbon element in the supercooled martensite dissolves back during the tempering process and forms cementite with low strength and hardness, resulting in low strength and hardness of the steel of Comparative Example 4 and decreased wear resistance.

[0047] Table 1 Composition of steels in Examples and Comparative Examples Table 2 Production process parameters of Examples and Comparative Examples Table 2 Table 3 Microstructure and performance indexes of the steels of the examples and comparative examples

Claims

1. Chromium-molybdenum-vanadium-titanium microalloyed wear-resistant steel, characterized in that: The chemical composition, by mass percentage, includes: C: 0.3-0.4%, Si: 0.1-0.3%, Mn: 1.5-2.0%, P≤0.015%, S≤0.005%, Als: 0.01-0.05%, Cr: 0.3-0.4%, Mo: 0.15-0.30%, V: 0.05-0.10%, Ti: 0.4-0.8%, N: 0.01-0.012%, and the balance is Fe and unavoidable impurities.

2. The chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel according to claim 1, characterized in that: The microstructure of the chromium-molybdenum-vanadium-titanium microalloyed wear-resistant steel includes more than 90% martensite by volume, with the remainder being ferrite; and contains micron-sized Ti (CN) hard particles larger than 1 μm and nano-sized Mo-Ti-V composite carbonitride precipitates smaller than 30 nm.

3. The chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel according to claim 1, characterized in that: The chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel has a yield strength of ≥1000 MPa, a tensile strength of ≥1100 MPa, an elongation of ≥8%, and a hardness HBW of 400-500.

4. The method for producing chromium-molybdenum-vanadium micro-titanium alloyed wear-resistant steel according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the set chemical composition of the steel, converter smelting, LF refining, RH refining, continuous casting, slab heating, rolling, laminar cooling, coiling and tempering can be carried out in sequence.

5. The production method according to claim 4, characterized in that: The steel slab after continuous casting is heated by hot delivery and hot charging. The temperature of the heated steel slab out of the furnace is 1200-1230℃, and the time in the furnace is 180-300 minutes.

6. The production method according to claim 4 or 5, characterized in that: The heated steel ingot is rolled in two stages. The final rolling temperature of the first stage is ≥1000°C, and the thickness of the intermediate ingot after rolling is 45-55 mm.

7. The production method according to claim 6, characterized in that: The finishing temperature of the intermediate billet in the second stage rolling is 850-890°C, and the thickness of the steel plate after rolling is 4-16 mm.

8. The production method according to any one of claims 4 to 7, characterized in that: After rolling, the steel plate is cooled in laminar flow. When the thickness of the steel plate is 4 to 10 mm, the steel plate is directly cooled to 150 to 250°C at a cooling rate of ≥30°C / s.

9. The production method according to any one of claims 4 to 7, characterized in that: When the steel plate thickness is 10.1-16 mm, two-stage cooling is adopted. First, the steel plate is cooled to 680-720°C at a cooling rate of ≥10°C / s, air-cooled for 2-4s, and then continued to cool to 150-250°C at a cooling rate of ≥30°C / s.

10. The production method according to any one of claims 4 to 9, characterized in that: The steel plate is tempered after coiling, with a tempering temperature of 580-620°C and a tempering time of 30-40 min.

Citation Information

Patent Citations

  • High-titanium wear-resistant steel and preparation method thereof

    CN109706399A